Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 3 - Section 3.6 - Derivatives of Logarithmic Functions - 3.6 Exercises - Page 223: 47



Work Step by Step

Given: $y =(cosx)^{x}$ Taking logarithmic on both sides of the function $y =(cosx)^{x}$ $lny=xln(cosx)$ Take implicit differentiation with respect to $x$. Apply product rule of differentiation. $\frac{d}{dx}(lny)=\frac{d}{dx}[xln(cosx)]$ $\frac{1}{y}\frac{d}{dx}(y)=x\frac{d}{dx}[ln(cosx)]+ln(cosx)\frac{d}{dx}(x)$ $\frac{d}{dx}(y)=y[x\times\frac{1}{cosx}\frac{d}{dx}(cosx)+ln(cosx)]$ $\frac{d}{dx}(y)=y[x\times\frac{1}{cosx}(-sinx)+ln(cosx)]$ Hence, $y'=(cosx)^{x}[ln(cosx)-xtanx]$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.